FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PENERAPAN PHBS RUMAH TANGGA DI LINGKUNGAN NELAYAN 2 WILAYAH KERJA PUSKESMAS SUNGAILIAT KABUPATEN BANGKA: Harmendo (JURNAL SMART ANKes, 2021)
PHBS in the household is an effort to empower household members to know, want and be able to carry out clean and healthy living behaviors and play an active role in the health movement in the community. The implementation of household PHBS in Fishermen's Environment 2 still needs attention, especially by Sungailiat Health Center where there is a decrease in coverage in 2020. This study aims to determine the factors related to the implementation of household PHBS in Fishermen's 2 Environment Working Area of ??Sungailiat Health Center, Bangka Regency. The type of research used in this research is analytic with survey method and cross sectional study approach. This research was conducted in Fishermen's Neighborhood 2 Bangka Regency. The population in this study were households in Fishermen's Environment 2, Bangka Regency, which amounted to 1,054 households, with a total sample of 99 respondents. Analysis of the data used includes univariate and bivariate analysis using the chi-square test. The results showed that there was a relationship between factors such as Knowledge (p = 0.002), Attitude (p = 0.000), Education (p = 0.000), Availability of Supporting Facilities (p = 0.001) and Family Support (p = 0.000) with the application of Household PHBS, while the income variable (p = 0.327) which means there is no relationship with the application of Household PHBS